Pengaturan Memperoleh Kembali Status Warga Negara Indonesia Bagi ISIS Eks WNI Ditinjau Dari Peraturan Pemerintah Nomor 2 Tahun 2007 dan Konsep Maslahah Mursalah - Saiful Bari (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2020)
This research is motivated by the loss of Indonesian citizenship status experienced by Indonesian citizens who are members of ISIS combatants. This is in line with of Article 23 letter e in Law No. 12 of 2006. The purpose of this study is to analyze the arrangements to regain the status of Indonesian citizens. This type of research is normative law. This study uses a law approach and the concept of the problem maslahah. The main material data of this study are from perimer legal material and secondary legal material. The results of this study conclude that first, in the perspective of the Citizenship Law and its implementing regulations, ex-ISIS former citizens are not eligible to regain Indonesian citizenship status as regulated by Article 9 of Law No. 12 of 2006 and Article 2 to Article 12 of PP No. 2 of 2007. Second, in the perspective of the problem maslahah, the Citizenship Act and its implementing regulations do not conflict with the sources and the propositions of Islamic law. Therefore, maintaining the sovereignty of the Unitary State of the Republic of Indonesia and the interests of the people by not giving them RI citizenship status is a beneficial act.